It happened one murder : a novel - Lawson, Liz, 1980- (Sourcebooks Landmark, 2026)
"Only Murders in the Building gets a rom-com twist in this laugh-out-loud mystery-romance following one woman who will have to pair up with an unlikely ally to solve a murder in their quaint New Jersey beach town, perfect for fans of Jesse Q. Sutanto, Elle Cosimano, and Katherine Center. Murder has a way of bringing people together... Harriet Baker thought that when she left Logan Island, she was leaving for good. But after getting fired from her dream magazine job, she finds herself stuck back in the sleepy New Jersey beach town, living with her eccentric mother and desperate to escape. And her ticket out might be...murder? When Harriet's extravagant birthday party ends with a dead body, all fingers point to Sara Allbright, the troublesome sister of none other than Nic, Harriet's short-lived fling from years ago that she's been eager to forget. And the feeling is entirely mutual. But murder makes for a good story, and when Harriet is told that she can get her old job back if she writes an article uncovering what really happened the night of her party, she readily agrees. To write her piece, Harriet will need Nic's full cooperation, and if Nic wants to clear his sister's name, he'll need Harriet's investigative skills. But working together? That's less than ideal. As the two team up to find the real killer, they'll discover the dark underbelly of their seemingly perfect hometown, uncover long buried feelings, and maybe, just maybe, realize that they might work well together after all"-- Provided by publisher.